Dimensionamento de tubos automotivos de poliamida e seleção de materiais a partir de uma perspectiva de sustentabilidade - Ramos, Wallyson Souza (2022)
The increase of using of polymers in automobiles became possible the decrease of fossil consume in the last years. This market is influenced significantly by fossil-based polyamides, as polyamide 12 that it is used to make fuel tubes. However, the development of bio-based polyamide (PA1010 and PA610) with higher mechanical resistance than PA12 create the possibility of reducing of weigh and environmental impacts after substituting of this. This work aims to reduce of CO2 emission along of automotive tube life cycle by substituting PA12 with PA1010 and PA610. We performed mechanical tests and difference scanning calorimetry for evaluating the mechanical and thermal properties of polyamides PA1010, PA610, blends PA1010/PA610 and PA12. Also, it was performed the life cycle assessment of automotive tubes with bio-based polyamides and PA12. We observed that yield stress and crystallinity degree of bio-based polyamides and blends was almost equal among them.The substitution of PA12 by PA610 and PA1010 provided a decrease in the weight of 20% and 32%, respectively. Regarding the emission of CO2, we observed a decrease of 34% for tubes of PA1010 and 40% for tubes of PA610.